Culture in a liquid modern world - Bauman, Zygmunt, 1925- (Polity ; In association with the National Audiovisual Institute, 2011)
"In its original formulation, 'culture' was intended to be an agent for change, a mission undertaken with the aim of educating 'the people' by bringing the best of human thought and creativity to them. But in our contemporary liquid-modern world, culture